The Effectiveness Of Traditional Games As A Media To Strengthen The Akhlak Of High School Students - Yanuarita Nur Hanifa; Siti Nurbayani; Wilodati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to determine the effectiveness of integrating traditional games as a medium to strengthen the noble akhlak of senior high school students. The dimensions of noble akhlak refer to the Pancasila Student Profile, including the dimensions of religious akhlak, personal akhlak, interpersonal akhlak, environmental akhlak, and national akhlak. This study uses a mixed-method with an Explanatory Sequential Design where quantitative studies are used as a reference to deepen the process through qualitative studies. Quantitative data collection techniques used questionnaires, while qualitative data collection techniques used semi-structured interviews, participant observation, and learning document analysis. Quantitative data analysis was conducted using descriptive quantitative analysis, and the significance of pretest and posttest differences was tested using the Wilcoxon Signed Rank Test. Qualitative data analysis used the Miles & Huberman interactive model, which was conducted through the stages of data reduction, data presentation, and conclusion drawing. This study quantitatively showed an increase in the average pretest and posttest scores for all dimensions, albeit within a small range. The learning intervention provided significant, uneven changes across all akhlak dimensions. Based on the qualitative studies, the results also demonstrated effectiveness in strengthening akhlak, particularly in the dimension of akhlak toward others, as it improved the quality of interactions between students and fostered meaningful learning experiences relevant to local culture. This research requires further research, particularly on the development of more accurate instrument evaluation with more complex learning designs and systemic support for sustainable implementation.